Can the Activities of Acetylcholinesterase and Glutathione S-Transferases of Crangon crangon (L.) be Used as Biomarkers of Fuel Oil Exposure? - Menezes, Salomé
This work aimed to determine the sensitivity of acetylcholinesterase (AChE) and glutathione S-transferases (GST) activities of Crangon crangon (L.) to the water-accommodated fraction (WAF) of the fuel oil spilled by the oil tanker Prestige, in order to assess their usefulness as markers for this kind of pollution. Laboratory exposure of shrimps to WAF of weathered Prestige fuel oil showed no significant interference with AChE activity. Significant induction of GST activity was observed, potentially as a result of high concentrations of polycyclic aromatic hydrocarbons. However, these results were only obtained with the higher WAF concentrations tested. It was concluded that AChE and GST activities of C. crangon were not useful biomarkers for short-term exposure to the WAF of fuel oil spilled by the tanker Prestige and carried to the beaches of Galicia (NW Spain).